Faculty members' comfort levels in utilizing high-fidelity simulation in a Bachelor of Science nursing program. - Jones AL (Faculty Members' Comfort Levels in Utilizing High-fidelity Simulation in a Bachelor of Science Nursing Program, 2005)
As recognized simulation experts, Seropian et al. (2004a), advised that faculty members who are comfortable utilizing high-fidelity simulation as a teaching methodology would facilitate the success of a simulation program. They recommended that faculty members be given adequate time to learn how to use simulation technology before they are expected to utilize it as an instructional methodology with students. Also, they stressed the importance of addressing curriculum issues with faculty members in the initial phase-in plan for teaching with simulation.The purpose of the study was to survey nursing faculty members' in a midwestern college of nursing as to their perceived comfort levels with utilizing high-fidelity simulation. Specifically, the study was to determine the faculty members' comfort level in utilizing high-fidelity simulation to teach nursing skills and evaluate nursing skill competency. Faculty members' perceptions of the time required to begin utilizing this new teaching methodology in their courses was also studied. Support services that would assist the faculty members to become more comfortable with high-fidelity simulation were the final area studied.The findings indicated the faculty members were not very comfortable utilizing high-fidelity simulation as a teaching methodology or for evaluation of skills. Faculty members who held a position of Assistant Professor were more comfortable utilizing high-fidelity simulation to promote time-on-task and teach nursing skills than were faculty members who held a position of Instructor. Furthermore, there was a positive relationship between faculty members' comfort level in utilizing simulation as a skill teaching methodology and their comfort level in utilizing it to evaluate nursing skills.A majority of the faculty members estimated they would require 0.5 Full-Time Equivalent (FTE) release for the semester to plan and implement simulation into their courses. A majority of the faculty members perceived it would require 0.25 FTE release for the semester to evaluate the use of simulation. Finally, they perceived the support systems of a simulation specialist and demonstrations with simulation to be the most helpful to them as they begin to utilize high-fidelity simulation.